Digital Communication Skills: Migrants and Cultural Identity - Melly Ridaryanthi; Kurniawan Prasetyo; Anindita Anindita; Nur Kholisoh (Jurnal Abdimas Perbanas, 2026)
The digital age has transformed how people communicate, access information, and build personal and professional networks. For many communities, particularly migrant workers and individuals in underserved areas, there remains a gap in digital literacy that hinders their ability to fully leverage the benefits of digital communication and intercultural communication competence. Despite widespread access to smartphones and the internet, many community members face challenges in effectively using digital tools for meaningful engagement, personal growth, and professional development. This community service program aims to equip participants with essential digital communication skills, enabling them to access valuable online information, maintain social connections, and develop personal branding strategies. The community service conducted towards Indonesia Migrant Workers in Penang, Malaysia. Participation of all attendees were very enthusiastic regarding the topic and gave feedbacks as necessary. This activity could cater the cognitive level of audiences by providing understanding regarding intercultural communication competence developed in using digital devices which beneficial for migrant workers. After the activity, audience could enhance digital literacy for accessing and evaluating online information, strengthen social connections through responsible digital communication, and improve intercultural communication competence.